Increased prevalence of obstructive sleep apnoea in patients with Charcot–Marie–Tooth disease: a case control study. Issue 7 (16th June 2008) - Dziewas, R; Waldmann, N; Böntert, M; Hor, H; Müller, T; Okegwo, A; Ringelstein, E B; Young, P
Abstract : Obstructive sleep apnoea (OSA) has previously been described in a large family suffering from Charcot–Marie–Tooth disease type 1 (CMT1). In the present study, we used a case control design to establish whether this suggested link between OSA and CMT1 may also be found when studying genetically non-related patients. 12 patients with CMT1 and 24 control patients matched for age, sex and body mass index (BMI) were included in the study. Neurological disability was graded with a previously established 6 point score. All patients underwent overnight polysomnography. The mean apnoea–hypopnoea index (AHI) of patients with CMT1 was 10.5 (16.3) which was significantly higher than that of the control group (1.5 (1.3)). Five out of 12 patients with CMT1 had an AHI ⩾10/h compared with 1 of 24 control patients (p<0.01). In patients with CMT1, a significant correlation between AHI and neurological disability was found (Spearman r = 0.62; p = 0.031) while BMI and age were not related to AHI. CMT1, in particular CMT1A, predisposes with disease progression to the development of OSA. Pathophysiologically, one may assume that CMT1 related pharyngeal neuropathy increases the collapsibility of the upper airway which in turn leads to recurring obstructive respiratory events.